A concise approach for interpreting the removal kinetic of 2,4-D by carbonized peanut shell - Gulen, Jale; Karpuz, Omer (TAYLOR & FRANCIS INC, 2026)
The present study displays the adsorption characteristics of dichloro phenoxy acetic acid (2.4-D) on biomass-based peanut shell (BPC) carbon. Experiments were conducted by varying some parameters like concentration, pH, and temperature. 2,4-D adsorption uptake was increased from 0.504 to 3.826 mg/g with rising concentration from 1 mu g/mL to 5 mu g/mL and giving the highest adsorption at acidic pH. 1.605 mg/g uptake was obtained at pH 2.7. The data were in good harmony with Langmuir, Freundlic, Dubinin-Radushkevich (DR), and Generalized isotherms. The monolayer adsorption capacity was found as 42.62 +/- 0.3257 mg/g. The kinetic was governed by the first-order kinetic. Various kinetic models were employed and particle diffusion was predominated for 2,4-D adsorption. Thermodynamics were explained in detail. The mean adsorption energy (E) was shown by the physical sorption, and Gibbs energy was the indicator of the spontaneous nature of the adsorption. Standard enthalpy, entropy, and Gibbs values were recorded as 5.064 +/- 139.84, 18.849 +/- 0.148, and 0,7414 +/- 0.0943 J/mol. The results showed that BPC was an eco-friendly and cost-effective material.
Keywords: Active carbon; adsorption; kinetic; peanut; 2.4-D; LOW-COST ADSORBENTS; ACTIVATED CARBON; AQUEOUS-SOLUTION; METHYLENE-BLUE; ADSORPTION-ISOTHERMS; WATER-TREATMENT; CHROMIUM VI; SORPTION; MODELS; PHENOL; Chemistry